Revisiting dollarisation hysteresis : evidence from Bolivia, Turkey and Indonésia - Freitas, Miguel Lebre de (2003)
In this paper, we pick up three countries with different inflation experiences and dollarisation levels and we investigate whether dollarisation exhibits different reversibility patterns, as suggested by the literature. The sample includes a country that experienced hyperinflation (Bolivia), a high inflation country (Turkey) and a country that experienced moderate to low inflation (Indonesia). By providing evidence of dollarisation hysteresis in these three countries, this paper challenges the view according to which this phenomenon is confined to highly dollarised economies or to economies that experienced high inflation rates for long periods of time.